2008
DOI: 10.1007/s00213-008-1098-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential regional and dose-related effects of asenapine on dopamine receptor subtypes

Abstract: These results indicate that asenapine has region-specific and dose-dependent effects on dopamine receptor subtypes in rat forebrain, which may contribute to asenapine's unique psychopharmacological properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 45 publications
11
46
0
Order By: Relevance
“…34,35 In addition, antagonism at 5HT 2A receptors, leading to an increase in dopamine activity in the prefrontal cortex, has also been suggested as a possible mechanism for alleviating negative symptoms 2,35 and enhancing cognition 36 in schizophrenia and other disorders. Findings from rat studies deduced that asenapine causes a dose-dependent increase in cortical 37 and hippocampal dopamine 37 , noradrenaline 38 and acetylcholine 38 comparable to previous reports with clozapine and quetiapine. Similarly, the 5HT 2C receptor may also have a similar role as 5HT 2A and its antagonism has been linked to improvement in negative symptoms.…”
Section: Pharmacology and Mode Of Actionsupporting
confidence: 84%
“…34,35 In addition, antagonism at 5HT 2A receptors, leading to an increase in dopamine activity in the prefrontal cortex, has also been suggested as a possible mechanism for alleviating negative symptoms 2,35 and enhancing cognition 36 in schizophrenia and other disorders. Findings from rat studies deduced that asenapine causes a dose-dependent increase in cortical 37 and hippocampal dopamine 37 , noradrenaline 38 and acetylcholine 38 comparable to previous reports with clozapine and quetiapine. Similarly, the 5HT 2C receptor may also have a similar role as 5HT 2A and its antagonism has been linked to improvement in negative symptoms.…”
Section: Pharmacology and Mode Of Actionsupporting
confidence: 84%
“…Asenapine was dissolved in 0.9% saline and administered subcutaneously (s.c.). Asenapine was given s.c. in an attempt to provide a surrogate for the sublingual route used in clinical studies [44], as well as for consistency with other preclinical studies that have assessed the effects of asenapine [15,23,53,54].…”
Section: Drugsmentioning
confidence: 99%
“…Based on preliminary tests with asenapine (0.003-0.1 mg/kg s.c.) that assessed effects on spontaneous locomotor activity, doses of asenapine (0.025, 0.05, and 0.075 mg/kg s.c.) were chosen that were expected to have minimal effects on motor function. The asenapine doses and s.c. route used in these studies were also based on studies demonstrating D 2 receptor occupancy in rat brain [46] and demonstrating antipsychotic-like activity in established neurochemical and behavioral paradigms [15,23,54]. Asenapine was administered 40 minutes before testing and 10 minutes before PCP or D-amphetamine.…”
Section: Studies 1a and 1b: Effects Of Acute Intervention On Deficitsmentioning
confidence: 99%
“…The asenapine doses selected are active in neurochemical and behavioural paradigms and were used for comparison with those studies (Franberg et al 2008;Tarazi et al 2008Tarazi et al , 2009. Gross motoric or weight effects are not observed with this treatment paradigm.…”
Section: Drug Treatment and Tissue Preparationmentioning
confidence: 99%
“…Preclinical studies have demonstrated that asenapine blocks the conditioned avoidance response (predictive of antipsychotic activity) without inducing catalepsy (predictive of extrapyramidal side-effects) (Franberg et al 2008). Repeated treatment with asenapine alters densities of dopamine, serotonin, and glutamate receptor subtypes in a fashion similar to that of second-but not first-generation antipsychotic drugs (Tarazi et al 2008(Tarazi et al , 2009.…”
Section: Introductionmentioning
confidence: 98%